ANALISIS PERENCANAAN REKRUTMEN TENAGA PENDIDIK DALAM PERSPEKTIF MANAJEMEN PENDIDIKAN ISLAM - Faisal, Mohamad; Hinggil Permana; Nur Rochimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the planning of teacher recruitment from the perspective of Islamic education management. The study is motivated by the challenges faced by Islamic educational institutions in conducting effective recruitment processes, such as the lack of needs-based planning, limited systematic documentation, and the tendency to use internal network-based recruitment which may reduce objectivity. This research employs a qualitative descriptive approach using a literature review method. Data were collected from national accredited journals and international indexed journals published between 2016 and 2026. The data were analyzed using content analysis to identify key themes related to recruitment concepts, implementation strategies, and managerial roles in Islamic education. The findings indicate that recruitment planning in Islamic education management emphasizes not only administrative processes but also the integration of spiritual values such as trustworthiness, fairness, and professionalism. The planning process includes needs analysis, determination of recruitment criteria, selection strategies, and evaluation mechanisms. However, in practice, many institutions still rely on informal recruitment systems that lack transparency and structured procedures. Therefore, systematic and competency-based recruitment planning is essential to improve the quality of educational institutions and produce professional and morally grounded educators.